KAJIAN HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN TERHADAP KASUS TABRAK LARI - Dita Aulia, Anwar Sadat Harahap (NERACA KEADILAN, 2023)
The large number of vehicles that are not accompanied by public awareness of safety and traffic order while driving is still an obstacle in Indonesia. Accidents that often occur on the road are often interpreted as suffering that befalls a person. Hit and-runs are usually considered a criminal offense because they involve violations of traffic laws and often involve injury or death of another person. Based on the problem formulation above, the aims of this research are: 1. To find out the factors that hinder the implementation of Law Number 22 of 2009 concerning Road Traffic and Transportation in hit-and-run cases, 2. To find out the types of sanctions applied to the perpetrators hit and run according to Islamic law and law number 22 of 2009 concerning traffic, 3. To find out the efforts made by law enforcement officials and the community to prevent hit and run cases. The location of this research was carried out at the Deli Serdang Police Station which is located at Jl. Sudirman No. 18 District. Lubuk Pakam, Kab. Deli Serdang, North Sumatra, Postal Code 20512. The type of research used in this research uses two types of approaches, namely a normative juridical approach and an empirical juridical approach. The types of data required in this research are primary data and secondary data. Sample distribution is the distribution of the average or proportion of samples taken repeatedly from the population. To obtain correct and accurate data in this research, literature study and field study procedures were carried out. Analysis of data processed from the literature is then analyzed descriptively qualitatively. Describe the data descriptively. Islam is a perfect religion whose teachings cover all aspects. In Indonesia, there is a Compilation of Islamic Law (KHI) which regulates various aspects of Islamic family law and Islamic civil law. The investigation carried out by the Deli Serdang Police Traffic Accident Unit which handled the hit-and-run accident was in accordance with the Regulation of the Chief of the Indonesian National Police Number 15 of 2013. Based on the description of the discussion of the problem in this scientific work, the following conclusions can be drawn: 1. From the perspective of Islamic law, this hit-and-run act can be subject to ta'zir. The criminal law for hit-and-run cases has provisions in Article 312 of Law Number 22 of 2009 concerning Road Traffic and Transportation, 2. Sanctions for hit-and-run perpetrators in the study of Islamic law are ta'zir punishment from social punishment, payment of a fine (diyat ), corporal punishment (hijab). Meanwhile, sanctions for perpetrators in criminal law are Article 231 paragraph 1 with a maximum imprisonment of 3 years or a maximum fine of IDR 75,000,000.00 (seventy-five million rupiah). 3. Prevention efforts from law enforcement and the community for cases In this hit and run, the law must provide strict sanctions to the perpetrator of the hit and run. This can include criminal penalties, steep fines, and vehicle impoundment.